Nilai Ekonomi dan Sosial Budaya Pembuatan Pisau dan Parang di Pulau Binongko - Laxmi; Samdin; Akifa; Muh. Reynaldi Ismail; Yoris Imanuel; Rizky Nur Amalia (Jurnal Ilmu Sosial dan Humaniora, 2025)
Binongko Island is known as the “Island of Blacksmiths” due to its knife and machete-making activities, which have been passed down from generation to generation. This descriptive qualitative study aims to understand the economic and socio-cultural values contained in these activities. The results show that the blacksmith industry is the main source of income for the community, but craftsmen face economic vulnerability due to fluctuations in raw material prices and dependence on the role of “collectors” who create patron-client relationships. Socio-culturally, this activity contains strong gender symbolism, where long machetes represent men and knives represent women, as well as the use of indigenous knowledge in testing product quality. Despite its deep philosophical and identity values, the blacksmith community in Binongko has experienced technological stagnation due to limited capital and inadequate electrical infrastructure. This condition creates a “subsistence trap” that hinders transformation towards the modern market. Marketing innovation strategies and capital strengthening are needed to maintain the sustainability of this cultural heritage while improving the economic welfare of the craftsmen.